Analisis Faktor Produksi Dalam Pengembangan Budi Daya Lebah Madu Klanceng (Trigona sp) Di Kampung Madu (Studi Kasus di Kecamatan Banjaranyar Kabupaten Ciamis Provinsi Jawa Barat) - Deffi Setiadi; Tuhpawana Priatna Sendjaya; Euis Dasipah (OrchidAgri, 2023)
Trigona sp. Bees, also known as bumble bees, are stingless bees and do not depend on bee pollen for their nutritional needs. The resin contained in the plant is needed for the production of propolis in the hive, so that Trigona sp can be cultivated anywhere with other types of bees. The aim is to find out the production factors that support the reproductive development of the klanceng honey bee (Trigona sp), the factors that influence the production of the klanceng honey bee (Trigona sp), and the factors that affect the income of the klanceng honey bee. (Trigona sp) influenced the research conducted. Factors affecting oyster production (Trigona sp) (land area, number of insects, equipment and labor wages). From the research results it is known that the variables of land area, number of insects, fixed costs and variable costs affect bee production, and from the results of multiple linear regression analysis the following equation is obtained, besides that the number of hives, fixed costs and variable costs that affect beekeeper income is variable, while land area has no effect. The results of the analysis of multiple linear regression tests produce the following equation, With any measure of commercial profitability, beekeeping is very profitable for agriculture.